BACTERIOLOGICAL QUALI TY OF HAND DUG WELLS IN MOSHIE ZONGO, KUMASI, GHANA - Issah, A.; Imoro, Z. A. (UDS International Journal of Development, 2019)
Water is life and good drinking water is good life. However, not all the populace of Ghana has access to treated piped water. The alternative sources of drinking water to piped water especially in deprived communities are hand dug wells, boreholes, dugouts and dams. However, the quality of these drinking water sources is questionable. Consequently, this study investigated wells in Moshie Zongo, Kumasi for indicator and pathogenic bacteria. Bacteria identifications were carried out according to standard techniques (Anon, 1992; American Public Health Association, 1995; Acumedia Manufacturers, 2011). The groups of bacteria identified in the sampled wells were total coliform, faecal coliform, E. coli and shigella spp. Total coliform counts ranged between 2.5x106 cfu/100 ml and 16.3x106 cfu/100 ml while faecal coliform counts ranged between 0.7x106cfu/100 ml and 13.2x106 cfu/100 ml. Also, E. coli and shigella spp. counts ranged from 0.87x104cfu/100 ml to 16.66x104 cfu/100 ml and from 0.4x105cfu/100 ml to 3.22x105cfu/100ml respectively. The presence of pathogenic bacteria in sampled wells is against the recommended standard by WHO for drinking water, therefore water from these wells were considered unsafe for drinking. Keywords: Bacteriological, Wells, Total, faecal Coliforms, E. coli, shigella spp.